Diffuse Thyroid Uptake in FDG PET/ CT Scan cCan Predict Subclinical Thyroid Disorders - Hasan, Mustafa R.; Kadam, Satar M.; Essa, Samar I. (Iraqi Journal of Science, 2022)
Background: 18F-FDG positron emission tomography (PET) has established itself in the field of oncology and it is useful in the initial staging and follow-up of a variety of malignancies. Significant thyroid uptake is often identified as an accidental finding on whole-body positron emission tomography for non-thyroid disease.Aim of this study: to investigate the effect of 18F-FDG on thyroid gland function after performing PET scan compared to thyroid function prior to scan.Materials and Methods: 43 subjects who had an 18F-FDG PET scan as part of a cancer screening program participated in this study. All cancers are diagnosed using 18F-FDG, except for prostate cancer, brain cancer and neuro-endocrine tumors, which are diagnosed using Ga-68. Thyroid stimulating hormone (TSH), thyroxine (T4), and triiodothyronine (T3) were measured.Results: Clinical information and results of thyroid function tests were available for 43 patients. Twenty- three out of 43 patients (53.48%) had abnormally high TSH levels with incident hypothyroidism, while 20 out of 43 patients (46.51%) had abnormally low TSH levels with incident hyperthyroidism, and the association was significant (p <0.05).Conclusion: Thyroid hormone abnormality is strongly associated with the degree of diffuse thyroid uptake on 18F-FDG PET. As a result, an autoimmune process could be the most likely pathological cause of diffuse thyroid uptake.